AN EVALUATION OF DIGITAL CONTENT ASSISTED LANGUAGE LEARNING ON FANS TO ENGLISH APPLICATION: A CASE STUDY ON SECONDARY SCHOOL IN MAKASSAR - Andi Hamzah Fansury (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
In learning foreign languages, especially learning English, the use of digital technology is a necessity, aimed at overcoming the problems that often occur when the teaching and learning process takes place, such as lack of lessons to increase student time in practising language skills, limitations of authentic learning material, and too many students' studies. The writer offers Digital Content Assisted Language Learning (DCALL) as a solution to teaching and learning English. Digital Content Assisted Language Learning (DCALL)is a new form of learning in the digital era recently. DCALL is a content-based learning digital in the form of writings, images, videos, and authentic material obtained from various sources such as the Internet, social media, blogs, email, vlogs, television and so on used to simplify the teaching and learning process. In this study, the researchers want to know the perceptions of teachers and students about Digital Content Assisted Language Learning (DCALL) on Fans to English applications. A qualitative study was applied in this study. The participants in this study were 100 students from secondary schools in Makassar. Questionnaires and interviews were used in this study to know about it. The result of this study was that teachers and students gave positive perceptions about implementing Digital Content Assisted Language Learning (DCALL) on Fans to English applications. Based on the evaluation results, the writer concludes that this application can be used in learning.